A novel highly dispersed tetra-metal nano heterogeneous ozone catalyst derived from microbial adsorption and in situ pyrolysis. (18th November 2020) - Xie, Jianping; Fan, Wei; Cui, Hao; Feng, Ningning; Wang, Guozhen; Wang, Hui; Liu, Xinxing; Qiu, Guanzhou; Wu, Haiyan
Abstract: In recent years, the pyrolysis of microbial biomasses that adsorb various metal ions has enabled the preparation of carbon-based polymetallic nanomaterials with excellent electrocatalytic and electrical energy storage properties. However, the preparation of ozone catalysts by this technique and the corresponding catalytic oxidation mechanism are still unclear. In this study, an Escherichia coli strain (BL21) was used for tetra-metal (Cu, Fe, Mn and Al) absorption and the obtained microbial biomass was pyrolyzed under the protection of a nitrogen flow at 700 °C and activated at 900 °C to prepare a microbial-char-based tetra-metal ozone catalyst (MCOC). This was used to degrade phenol and coking wastewater and exhibited a strong catalytic capability for coking wastewater, whose chemical oxygen demand removal efficiency of 70.86% is 16.7% higher than that of pure ozone and 14.67%, 7.21% and 3.58% higher than that of three commercial catalysts, respectively. It also improved the efficiency of ozonation for phenol by 33%. The MCOC was characterized by x-ray diffraction, x-ray photoelectron spectroscopy, scanning electron microscopy–energy-dispersive spectroscopy, transmission electron microscopy and other methods. The results demonstrated that the spherical metal nanoparticles had sizes ranging from 3 nm to 7 nm and that crystals of Fe2 O3 and Fe3 P were observed. The study showed that the MCOC promoted the production of more hydroxyl radicals and superoxides from ozone, which attack organics. The oxygen vacancies of the catalyst were also investigated. It was proved that the Lewis acid sites on the surface of metal oxides are the active centers of ozone decomposition. Therefore, this work provides a new method for the synthesis of multi-metal nanocomposites and expands the application of biosynthetic nanomaterials.